Current evidence on DNA aneuploidy cytology in noninvasive detection of oral cancer. (February 2020) - Shi, Linjun; Wang, Yufeng; Li, Chenxi; Liu, Wei
Abstract: DNA-aneuploidy cytology as a promising noninvasive tool in diagnosing oral precancer and cancer has been proposed in 2015. In this letter, we identified 9 studies on DNA aneuploidy cytology with special emphasis on using fresh tissue sample in detection of oral precancer and cancer. Evidence was updated as follows, for detection of OSCC in general oral lesions, the pooled sensitivity and specificity was 84.8 and 99.0 respectively; for discrimination of dysplasia and OSCC form oral lesions, the sensitivity and specificity was 75.7 and 76.8 respectively. On the whole, current evidence on the theme is not robust, and multicenter prospective studies are needed to consolidate the evidence.